2015
DOI: 10.5897/ajar2013.8209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar application on microbial biomass and enzymatic activities in degraded red soil

Abstract: To assess biochar effect on soil microbial biomass, community and enzymatic activities, degraded acidic soil was amended with three different rates (0.5, 1.0 and 2.0%) of oak wood biochar (W 0.5 , W 1.0 and W 2.0 ) and bamboo biochar (B 0.5 , B 1.0 and B 2.0 ), with control as 0%. The soil and the biochar were mixed thoroughly, wetted and incubated at a constant temperature of 25°C. The amended soil properties were evaluated after the 1st, 8th and 16th weeks of the incubation. It was found that soil pH, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The application of biochar (pyrolysis d at 600°C) to soil was improves soil organic carbon and soil pH and would have an effects on soil enzymes, microbial biomass for soil quality. It was found that soil pH, total organic carbon and urease increased significantly with increasing biochar rate (Walelign and Mingkui 2015).…”
Section: Introductionmentioning
confidence: 96%
“…The application of biochar (pyrolysis d at 600°C) to soil was improves soil organic carbon and soil pH and would have an effects on soil enzymes, microbial biomass for soil quality. It was found that soil pH, total organic carbon and urease increased significantly with increasing biochar rate (Walelign and Mingkui 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Spearman's correlation coefficients between the selective soil chemical and biological properties (n=3) Table 1. study of Demisie and Zhang (2015), the application of oak wood biochar and bamboo biochar at the same doses (1 and 2%) did not significantly increase the phosphatase activity. However, these authors found significantly higher values of phosphatase activity in the analysed soils (from 115 to 149 µg pNP g -1 DM h -1 ).…”
Section: Ta B L E 2 Average Number Of Microorganisms In Soil After Tmentioning
confidence: 80%
“…It was observed that the amendment of GAS residues significantly elevated soil N (including TN, NH 4 -N and NO 3 -N) content and pH, while significantly decreased AP content especially at high amendment levels. The input of N would increase the activity of ACP, while the elevation of soil pH would substantially decrease the activity of ACP 74,75 . These results probably indicate that there is a threshold of soil pH, which determines the activity of ACP influenced by addition of N and elevation of soil pH.…”
Section: Amendment Effect On Bacterial Community Structure Gemmatimomentioning
confidence: 99%